Inverse Cosine of Imaginary Number

From ProofWiki
Jump to navigation Jump to search

Theorem

$\cos^{-1} x = \pm \, i \cosh^{-1} x$


Proof

\(\displaystyle y\) \(=\) \(\displaystyle \cos^{-1} x\)
\(\displaystyle \implies \ \ \) \(\displaystyle \cos y\) \(=\) \(\displaystyle x\) Definition of Inverse Cosine
\(\displaystyle \implies \ \ \) \(\displaystyle \cosh \paren {i y}\) \(=\) \(\displaystyle x\) Cosine in terms of Hyperbolic Cosine
\(\displaystyle \implies \ \ \) \(\displaystyle i y\) \(=\) \(\displaystyle \cosh^{-1} x\) Definition of Inverse Hyperbolic Cosine
\(\displaystyle \implies \ \ \) \(\displaystyle y\) \(=\) \(\displaystyle - i \cosh^{-1} x\) multiplying both sides by $-i$

$\blacksquare$


Sources